Diatom-based inference of Asian monsoon precipitation from a volcanic lake in southwest China for the last 18.5 ka. (15th February 2018) - Li, Yanling; Chen, Xu; Xiao, Xiayun; Zhang, Hucai; Xue, Bin; Shen, Ji; Zhang, Enlou
Abstract: Diatom in the volcanic lake provides proxy evidence for pH changes that are characterized by variations in the percentage of acidophilous diatom species. The information regarding the hydrology of the lake, derived from a previous publication and survey of one year on the lake, indicate that pH is low during the wet season and higher during the dry season. Therefore, variations in lake water pH may be considered as a proxy record for past changes in precipitation. In the sediment, high/low relative abundance of acidophilous diatom species indicates high/low precipitation. The diatom record of the past 18.5 ka BP shows that precipitation decrease during the periods 17.0–15.0, 13.3–11.3, and 0.7–0.3 ka BP corresponding to the Heinrich Event 1 (H1), the Younger Dryas cold event (YD), and the Little Ice Age (LA). A marked precipitation increase between 15.0 and 14.5 ka BP occurred at the end of H1 and before the Bølling-Allerød (BA), which indicates a strong pre-Bølling wetting. The start of the Holocene is recorded at 11.3 ka BP. The climate was the wettest between 11.3 and 7.5 ka BP., then the wetter between 7.5 and 3.4 ka BP. Between 3.4 and 0.7 ka BP, the precipitation decrease in general, but in the period from 1.3 to 0.8 ka BP the precipitation was higher corresponding to the Medieval Warm Period (MWP). Our results support the hypothes that the Indian Summer Monsoon (ISM) was strongest during the Early Holocene. Highlights: A lacustrine diatom sequence recorded climatic fluctuations in SW China over the past 18.5 ka BP. The percentages of acidophilous diatoms are used as a proxy record for precipitation changes. The diatom record suggests that the Indian Summer Monsoon was stronger during the early Holocene.